Analysis of the process of treatment and care of a patient with a chest injury as a result of fall from height during kitesurfing – a case study - Terech, Sylwia; Książek, Janina; Piotrkowska, Renata; Kruk, Agnieszka (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
Aim of the study: The purpose of the paper was to study the case of a patient who had suffered a chest injury as a result of a fall from height. Material and methods: The study used the methods of document analysis and case study. The medical history and patient care process were analyzed. In addition, history taking and participant observation were utilized to deepen the whole. Conclusions: 1. The key problems for a patient with multiple body injuries are the sudden limitation of self-reliance with respect to self-care and self-management as well as concern about restoring full function after the treatment is completed. 2. Broadening society’s knowledge related to the use of sports equipment, increasing emphasis on learning how to safely drive a car or other vehicles and promoting cautiousness can contribute to reducing the risk of injuries.